A Rigid–Soft Graded Organic–Inorganic Interlayer for Durable and Corrosion-Resistant Zinc Anodes - Wang, Zhiyu; Cao, Junlun; Yang, Zixuan; Cheng, Jianli; Liu, Dan; Lei, Weiwei (Nano-Micro Letters, 2026)
Aqueous zinc (Zn)-ion batteries hold great promise as renewable energy storage system for carbon–neutral energy transition. However, Zn anodes suffer from poor Zn plating/stripping reversibility due to Zn dendrite growth and side reactions. Existing Zn interfacial modification strategies based on single-component or homogeneous structure are insufficient to address these issues comprehensively. Herein, we rationally designed an organic–inorganic hybrid interfacial layer with rigid-to-soft graded structure for dendrite-free and stable Zn anodes. A liquid plasma-assisted oxidation technology is developed to rapidly construct a porous ZnO inner framework in situ. This ZnO layer offers high interfacial energy, mechanical robustness, and an open structure that facilitates ion transport while firmly anchoring a subsequently coated soft polymer layer. The resulting architecture presents a structurally graded and functionally complementary interface, enabling effective dendrite suppression, continuous Zn ion transport, and enhanced corrosion resistance. As a result, a long cycling stability of more than 6000 h can be achieved at 1 mA cm−2 for 1 mAh cm–2 in symmetric cells. When used as anodes for zinc-iodine full battery, the hybrid interlayer can effectively prevent the Zn anodes from the corrosion by polyiodine, enabling stable cycling and negligible capacity decay (~ 0.02‰ per cycle) for over 10,000 cycles at 2.0 A g−1. This work demonstrates a promising interfacial design strategy and introduces a novel liquid plasma-assisted oxidation route for fabricating high-performance Zn anodes towards next-generation aqueous batteries. Highlights: 1 A hybrid interfacial layer with a rigid-to-soft graded structure and functionally complementary composition. 2 A facile and scalable liquid plasma-assisted oxidation process for preparing the porous ZnO inner layer. 3 Good cycling stability of zinc anodes for more than 6,000 h at a current density of 1 mA cm−2 for 1 mAh cm−2 and ultra-low capacity decay (~0.02‰ per cycle) for over 10,000 cycles for zinc-iodine battery.